Dinamika Komitmen Mahasiswa Teologi dalam Menjalani Panggilan Pelayanan - Batolu, Delpianti; Yokiman, Junni; Sopang, Oskar (APOSTOLOS, 2025)
The vocational commitment of theology students is not static; it evolves over time due to a variety of internal and external influences. This study aims to identify and analyze the factors that influence changes in the pastoral vocation commitment of theology students. Employing a descriptive quantitative method, data were collected through a structured questionnaire distributed to 31 theology students of Star’s Lub Theological College. The data were analyzed using descriptive statistics to obtain mean values across seven indicators. The findings show that faith conviction and family support had the highest scores, while spiritual experience and the influence of the church environment were comparatively lower. Some students expressed doubts about becoming pastors, suggesting cognitive dissonance between vocational ideals and the practical realities of ministry. It is concluded that vocational commitment is shaped by the integration of personal faith, emotional maturity, and supportive social contexts. The study recommends that theological institutions strengthen reflective spiritual formation and contextual mentoring programs to sustain students’ ministry commitment.